Learning, Design, and Technology 2016
DOI: 10.1007/978-3-319-17727-4_3-1
|View full text |Cite
|
Sign up to set email alerts
|

What Massive Open Online Course (MOOC) Stakeholders Can Learn from Learning Analytics?

Abstract: Massive Open Online Courses (MOOCs) are the road that led to a revolution and a new era of learning environments. Educational institutions have come under pressure to adopt new models that assure openness in their education distribution. Nonetheless, there is still altercation about the pedagogical approach and the absolute information delivery to the students.On the other side with the use of Learning Analytics, powerful tools become available which mainly aim to enhance learning and improve learners' perform… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Deciding to use the number of days active as the most efficient measure metric for effort over time from the log files is based on two reasonings: (a) supporting literature such as the research studies by Khalil and Ebner [13] and Kloft et al [14]. And (b) exploratory examination of correlations, knowledge of the problem domain, and examining descriptive statistics for the variables as the following.…”
Section: Measure For Effort Over Timementioning
confidence: 99%
See 1 more Smart Citation
“…Deciding to use the number of days active as the most efficient measure metric for effort over time from the log files is based on two reasonings: (a) supporting literature such as the research studies by Khalil and Ebner [13] and Kloft et al [14]. And (b) exploratory examination of correlations, knowledge of the problem domain, and examining descriptive statistics for the variables as the following.…”
Section: Measure For Effort Over Timementioning
confidence: 99%
“…Learning analytics studies in MOOCs have found that MOOC participation rate varies to a larger degree than for traditional higher education [4]. The dropout rate is also much higher in MOOCs than in traditional university courses [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the frequency with which reference is made to the notion of consent and informed consent (e.g., Dawkins, 2016;Hoel & Chen, 2016;Khalil & Ebner, 2016;Roberts, Howell, Seaman, & Gibson, 2016) • Formal consent should be obtained before data are collected/analyzed;…”
Section: Consent As a Notional Requirement?mentioning
confidence: 99%
“…Research in e-Learning today focusses not so much on new technology but on how material has to be prepared to be successful, and how students use it (Khalils and Ebner, 2016;Taraghi et al, 2013). This is also explained clearly in Serdyukov (2015).…”
Section: E-learning After 2000mentioning
confidence: 99%